UTILISATION STUDY OF ORAL HYPOGLYCAEMIC MEDICINES AT A TERTIARY CARE HOSPITAL - Siddiq, Abubaker; DR, Bharathi (Journal of Biomedical and Pharmaceutical Research, 2019)
Drug utilization research establishes the current trend in the use of antidiabetic drugs including the new drug and to identify irrational prescription. India has a sizeable Diabetic Population with more than 72 million type-2 diabetic patients. Glycemic control remains the major goal for prevention of complications arising from diabetes. Poor glycemic control can be prevented by using rational & safe use of anti-diabetic drugs. A prospective observational study was carried out for a period of three years with the aim to study drug utilization evaluation of Oral Hypoglycaemic Medicines. A total of 468 patients were enrolled with the inclusion criteria of patients with past history of diabetes as well as newly diagnosed cases. The study showed that diabetes is more prevalent in females than males and also found a higher prevalence of the disease among elderly patients. The study revealed the use of Metformin as the most commonly utilized drug among diabetic population. Glimeperide and Metformin were the most commonly prescribed anti-diabetic combination. The results of this study provide real-life data, which will help to formulate newer strategies to improve delivery of diabetes care. Key words: Diabetes, Drug Utilisation, Prospective, Prevalence